Distribution, Diversity, and Abundance of Nitrite Oxidizing Bacteria in the Subterranean Estuary of the Daya Bay - Sun, Wei; Jiao, Lijing; Wu, Jiapeng; Wei, Mingken; Hong, Yiguo (Frontiers in Marine Science, 2022)
The oxidation of nitrite to nitrate as the second step of nitrification is vital for the global nitrogen cycle, and the genus Nitrospira is the most widespread nitrite-oxidizing bacteria (NOB) in diverse natural ecosystems. However, our understanding of Nitrospira distribution and their response to dynamic environmental parameters is still limited in the subterranean estuary (STE), a special environment of mixed zone between land and sea. In this study, Nitrospira communities were collected within 5-10 cm depth intervals of sediments with the physiochemical gradients along the transections of the Daya Bay (DYB) from the landward member to the seaward member. The abundance, community structure of Nitrospira and their potentially influencing environmental factors were investigated using Q-PCR, the high throughput sequencing targeting Nitrospira nxrB gene and biostatistics analyses. The abundance of Nitrospira showed uniform distribution along the transections, but significantly decreasing variations were observed from the surface (<20 cm) to the bottom (>20 cm) of sediments. The community diversity and structure of Nitrospira also displayed remarkably vertical distribution in the DYB (STE), although no significant differences were observed along the transections of STE. Nitrospira marina (N. marina) predominated in the sediments, Candidatus Nitrospira bockiana (Ca. N. bockiana) and Candidatus Nitrospira defluvii (Ca. N. defluvii) were the main Nitrospira species, and Candidatus Nitrospira lenta (Ca. N. lenta) and Nitrospira japonica (N. japonica) also existed with relatively low abundance in the DYB (STE). These findings revealed that Nitrospira species (Ca. N. defluvii, Ca. N. lenta and N. japonica) derived from activated sludge was also widespread in natural habitats, and deduced that the STE may be affected by the pollution derived from terrigenous human activities. Statistical analysis combined with the STE dynamic variation indicated that dissolved organic carbon (DOC), salinity and ammonium along the sediment depths attributed to the vertical community distribution of Nitrospira species. In summary, the vertical distribution of Nitrospira and their response to the dynamic physiochemical parameters imply their important role in the nitrite oxidation of the STE and provide insights into the niche differentiation and diversely physiologic metabolism of NOB.